2014
DOI: 10.4111/kju.2014.55.11.725
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Ideal Core Number for Ultrasound-Guided Prostate Biopsy?

Abstract: PurposeWe evaluated the utility of 10-, 12-, and 16-core prostate biopsies for detecting prostate cancer (PCa) and correlated the results with prostate-specific antigen (PSA) levels, prostate volumes, Gleason scores, and detection rates of high-grade prostatic intraepithelial neoplasia (HGPIN) and atypical small acinar proliferation (ASAP).Materials and MethodsA prospective controlled study was conducted in 354 consecutive patients with various indications for prostate biopsy. Sixteen-core biopsy specimens wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…En una revisión sistemática donde se analizaron 87 estudios con un total de 20,698 pacientes, se encontró que las biopsias que toman 12 cilindros representan el equilibrio entre la detección del cáncer y los eventos adversos y que la toma de más de 12 muestras no genera un beneficio significativo. 33,34 Se encontró una asociación estadísticamente significativa entre el porcentaje de compromiso tumoral en biopsias y el valor de PSA, hallazgo similar a lo descrito por Bang Shim y cols. 35 Dentro de los hallazgos de este estudio, se pudo evidenciar dificultad al momento de la obtención de la información debido a un registro incompleto en las historias clínicas de algunas variables como porcentaje de volumen tumoral, diagnóstico clínico, examen digital rectal, volumen por ecografía, puntaje de Gleason e Invasión capsular.…”
Section: Discussionunclassified
“…En una revisión sistemática donde se analizaron 87 estudios con un total de 20,698 pacientes, se encontró que las biopsias que toman 12 cilindros representan el equilibrio entre la detección del cáncer y los eventos adversos y que la toma de más de 12 muestras no genera un beneficio significativo. 33,34 Se encontró una asociación estadísticamente significativa entre el porcentaje de compromiso tumoral en biopsias y el valor de PSA, hallazgo similar a lo descrito por Bang Shim y cols. 35 Dentro de los hallazgos de este estudio, se pudo evidenciar dificultad al momento de la obtención de la información debido a un registro incompleto en las historias clínicas de algunas variables como porcentaje de volumen tumoral, diagnóstico clínico, examen digital rectal, volumen por ecografía, puntaje de Gleason e Invasión capsular.…”
Section: Discussionunclassified
“…The question remains as to what the optimal number of biopsy cores should be. The study by Chambo et al [ 13 ] showed that at least 10-core biopsies may be needed in patients with low-risk prostate cancer. Adopting this concept, the present study recruited only patients who underwent biopsies of more than 10 cores.…”
Section: Discussionmentioning
confidence: 99%
“…A definitive diagnosis of cancer depends on the histopathological analysis of a core needle biopsy sample. In one prospective study, the negative rate of a 12-core biopsy technique was found to be more than 30% [ 20 ].…”
Section: Discussionmentioning
confidence: 99%